Mobility, inequality and choice: Circulation on the border of Haiti and the Dominican Republic. Issue 1 (1st July 2018) - Taylor, Erin
The 'mobility' in 'socio-economic mobility' is no mere metaphor. Rather, it is indicative of the intrinsic connection between social status and the circulation of resources. However, it would be a mistake to suggest that mobility is an all-in-one solution to inequality. The question of who benefits from the movement of people, things and information depends on what choices are available to people, how they are able to combine them and whether those choices can be successfully deployed to meet the goals they have set. I show how the relationship between mobility and inequality affects the choices people make in their everyday lives. For Haitians and their relatives living in the border zone of Hispaniola, mobility is a necessary livelihood strategy, but it comes with problematic social and economic implications. First, I provide an overview of the relationship between mobility and inequality. Second, I introduce the field site, a poor cross-border region on the southern border of Haiti and the Dominican Republic. Third, I demonstrate how Haitians' experiences of mobility and inequality affect their choices. I conclude by discussing how we can build a picture of mobility and inequality that responds more to the complexities of people's lives.